EXPLORING THE ROLE OF AI-ASSISTED LANGUAGE LEARNING IN ENHANCING SECOND LANGUAGE ACQUISITION AND LEARNER MOTIVATION (Qualitative Research Journal for Social Studies, 2026)
The rapid integration of artificial intelligence (AI) in educational settings has transformed language learning by providing adaptive feedback, interactive communication, and personalized learning pathways. This study explores the role of AI-assisted language learning in enhancing second language acquisition (SLA) and learner motivation among English as Second Language (ESL) learners. Specifically, the research investigates how AI-powered tools support language skill development, influence learner engagement, and foster autonomous learning practices. A mixed-methods research design will be employed to obtain a comprehensive understanding of both learning outcomes and motivational changes. The quantitative phase will adopt a quasi-experimental pretest–posttest design, involving two groups of ESL learners: an experimental group using AI-assisted language learning tools (e.g., AI writing assistants, conversational chatbots, and adaptive vocabulary platforms) and a control group receiving traditional instruction. Language proficiency gains will be measured through standardized skill-based assessments focusing on writing accuracy, vocabulary acquisition, and speaking fluency. Learner motivation will be examined using a structured questionnaire grounded in self-determination theory, assessing intrinsic motivation, engagement, and perceived autonomy. The qualitative phase will complement quantitative findings through semi-structured interviews and reflective learner journals to explore students’ experiences, perceptions of AI feedback, and motivational shifts during AI-supported learning. Quantitative data will be analyzed using descriptive and inferential statistics, including paired and independent sample tests, while qualitative data will be examined through reflexive thematic analysis to identify recurring patterns related to learner autonomy, engagement, and perceived effectiveness. The study is expected to demonstrate that AI-assisted language learning enhances second language acquisition by providing immediate feedback, increased practice opportunities, and personalized support, while simultaneously improving learner motivation and autonomy. The findings will contribute to the growing body of research on AI-mediated language education and offer pedagogical implications for integrating AI tools into ESL classrooms to support both cognitive and affective dimensions of language learning.